A case of spontaneous haematoma from vertebral artery arterio-venous fistula in a patient with neurofibromatosis type 1. (2nd November 2017) - Narayanamurthy, Harsha; El-Badawy, Sarah; Mukonoweshuro, William; Whitfield, Peter
Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by a mutation on chromosome 17. Vascular abnormalities are recognised complications of NF1. These include aneurysms, stenoses, arteriovenous malformations, fistulae, etc. We report the case of a young gentleman with NF1 with a spontaneous cervical bleed from an arteriovenous fistula arising from the left vertebral artery, and illustrate the various management options and difficulties arising from rapid fistula formation.